PREDIKSI KESULITAN LIKUIDITAS BANK DI INDONESIA - Muslim, Muslim; Gumanti, Tatang Ary; Sukarno, Hari (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract: This research aims to analyze the ability of Capital, Assets, Management, Earnings, Liquidity (CAMEL) ratio in differentiating and predicting the liquidity problem of the banks. The population of this research was national commercial banks listed on the Directory of Bank Indonesia from 2010 to 2013. The analysis tools used were the mean different test and logistic regression analysis. The results of the different test show that Adversely Classified Assets (ACA), Return on Equity (ROE), Loan to Deposit Ratio (LDR), and Non-Performing Loan (NPL) wereable to differentiate between the liquid and non-liquid, while Capital Adequacy Ratio (CAR), Fixed Assets against Capital (FAAC), Return on Assets (ROA), Operating Expenses to Operating Income (OEOI), and minimum deposit of rupiah were not the discriminators ofthe bank liquidity problem. The results of logistic regression analysis show that in 2011 the predictors used to predict the liquidity problem of the banks were the ratio of ACA and ROA, while in 2012,the ratios were CAR and ACA ratio and in 2013, it was only the CAR ratio. The pooling data, ACA and ROA, can be used as the predictor of the ability to predict the liquidity problem of banks in the future. Keywords: Liquidity Problem,Capital, Assets, Management, Earning, Liquidity